Development and evaluation of Standard Operating Procedures (SOPs) for quality control tests and radiological protection activities in a Nuclear Medicine Service - Krempser, Alexandre R.; Soares, Alexandre B.; Corbo, Rossana (Revista Brasileira de Física Médica, 2015)
The quality management in Nuclear Medicine Services is a requirement of national and international standards. The Brazilian regulatory agency in health surveillance, the Agência Nacional de Vigilância Sanitária (ANVISA), in its Resolução de Diretoria Colegiada (Collegiate Directory Resolution) nº 38, requires the elaboration of documents describing the technical and clinical routine activities. This study aimed to elaborate, implement and evaluate Standard Operating Procedures (SOPs) for quality control tests and radiological protection activities in the Nuclear Medicine Service of a university hospital. Eighteen SOPs were developed, involving tasks related to dose calibrator, gamma camera, Geiger-Müller detectors and radiological protection activities. The performance of its application was evaluated for a period of six months. It was observed a reduction in 75% of reported operational errors and 42% of the number of reported incidents with contamination by radioactive material. The SOPs were adequate and successful in its application. New procedures involving clinical activities will also be developed and evaluated.